THE RELATIONSHIP OF CORE STRENGTH WITH SELECTED PHYSICAL AND SKILL-RELATED ABILITIES IN FOOTBALL - Hussein Ahmed Salman; M. Hashim Mutab Taha (Journal Olahraga Rekat (Rekreasi Masyarakat), 2025)
Background. This study investigates the relationship between core strength and selected physical and skill-related abilities in football among junior players enrolled in the Football School for Sports Talent Development in Basra during the 2024–2025 academic year. Core strength is widely recognized as a fundamental component of athletic performance, playing a crucial role in stability, movement efficiency, and injury prevention. However, its direct impact on football-specific abilities requires further exploration. Objectives. The primary objective of this research was to identify the correlation between core strength and the development of physical and technical abilities essential for football performance. Method. The researchers employed the descriptive method with a survey approach, as it was appropriate for the nature of the variables and the research objectives. A purposive sample of 25 junior players from the National Center for Sports Talent Development was selected to represent the research population. Data collection involved a specialized questionnaire validated by experts, alongside a researcher-designed test to measure core strength. The data were statistically analyzed using the SPSS program. Results. The results demonstrated a significant relationship between core strength and selected physical abilities (such as balance, agility, and endurance), as well as skill-related abilities (including ball control, passing accuracy, and shooting precision). Players with stronger core muscles exhibited superior physical performance and more efficient execution of football-specific skills. Conclusion. In conclusion, the study emphasizes the importance of core strength in enhancing both physical and technical performance in football. The researchers recommend integrating core-strengthening exercises into training programs to optimize athletic development and competitive success.